The effect of water, urea, sodium hydroxide, and hydrogen peroxide processing on the cumin residues animal digestibility - Farkhondeh Rezaii; Javad Bayatkouhsar; Farzad Ghanbari; Fatemeh Arab (International Journal of Recycling of Organic Waste in Agriculture)
Purpose No research has been published on the effect of chemical processing on the degradability and nutritional value of cumin residue. Chemical processing, such as urea, sodium hydroxide, and hydrogen peroxide, has been widely investigated to increase the nutritional value of grain residues, but information on cumin residue is limited. The effects of untreated and treated (water, sodium hydroxide, urea, and alkaline hydrogen peroxide) cumin residue on the ruminal digestibility and chemical composition were investigated in this study.Method After treating cumin residues with the abovementioned chemical compounds, the chemical composition was evaluated with the standard procedures. Batch culture and gas production procedures were used to test the digestibility and gas production of treated and untreated cumin residue.Results The chemical compositions of cumin residues were significantly altered by chemical treatments (P< 0.05). Processing cumin residues with urea, hydrogen peroxide, and sodium hydroxide reduced the dry matter (DM) compared to the control treatment (P< 0.01). Processing cumin residues with sodium hydroxide significantly reduced DM digestibility compared to the control. The highest levels of DM digestibility and microbial mass production were also found in water treatment. Urea treatment increased the yield of microbial mass-produced compared to other treatments (P< 0.01).Conclusion In general, water and urea treatments increased the cumin residue digestibility more than other treatments, but sodium hydroxide and hydrogen peroxide treatments did not increase the cumin residue digestibility as expected.